Interstice as the new foundation of contemporary society’s urban design - Arze Arce, Gonzalo Horacio (Revista de Urbanismo, 2014)
Clearly the pressures of the modern world (characteristic of globalization, information technology, capitalism, individualism, etc.), have significantly transformed the way how are representing the condition of urban space. This process has been commissioned to strongly mark the boundary between a condition and another, with the private sphere and constantly engulfs prevailing public sphere. This article aims on the one hand, to establish some criteria to reflect the concept of interstice and position in a frame where contemporary society operates and develops. Moreover, through three different cases together and specificities, and reflects evidence from a space constituted the traditional way, it is possible to outline approaches that go beyond the physical conditions and reconfigure depending on the interstice. The conditions only oriented formal and functional physical resolution is insufficient to understand contemporary society. Therefore, it comes as prevailing criteria, participatory self, key in guiding new ways to occupy and understanding space, considering the perceptual user deployment allowing more flexible, adaptable and multifunctional environment. It is here that the constant interstice appears as a possibility to approach the understanding of this duality that seems unresolved.